Macular disease research in the United Kingdom 2011–2014: a bibliometric analysis of outputs, performance and coverage. (December 2015) - Royle, Pamela; Waugh, Norman
Abstract Background Bibliometric indicators, based on measuring patterns of publications and citations, are widely used by universities and research funders to assess research performance. Our aims were to: (1) perform a bibliometric analysis of UK macular disease research publications from 2011 to 2014 and compare this with the other countries producing major output in the area, and (2) compare the pattern of UK macular disease publication with the priorities for age-related macular degeneration (AMD) developed by the Sight Loss and Vision Priority Setting Partnership (SLV-PSP). Methods We used the Scopus database to retrieve macular disease articles published from 2011 to 2014. Citations to articles from 2011 to 2013 and journal impact factors (JIFs) for 2014 articles were obtained. Articles with UK authors were allocated to the 10 SLV-PSP priorities for age-related macular degeneration (AMD), where possible. Results The UK, USA, and Germany and China were the top four producers of macular disease research from 2011 to 2013. All except China had a higher proportion of citations than articles. There were 421 articles with UK authors published from 2011 to 2014, of which 49 % had international collaborators. The UK produced 9.7 % of the world's output of macular disease articles from 2011 to 2013, but received 14.2 % of the world's share of citations. UK authors' share of the world's top 10 % of cited publications from 2011 to 2013 was 16.2 %. In 2014, 13.2 % of UK articles were in journals in the top 10 % when ranked by Journal Impact Factors (JIFs), while the overall UK article share for that year was 9.9 %. UK articles did not show a strong correlation between citations and JIFs. The SLV-PSP published a set of 10 priorities for research into age-related macular degeneration in October 2103. Only 8 % of the UK's 2011–2014 publications matched the SLV-PSP top priority (treatment to stop dry AMD progressing) and 34 % did not match any of the SLV-PSP priorities, mainly because the priorities did not include invasive treatment of wet AMD. Conclusions The UK is performing well in macular research, based on bibliometric indicators. The distribution of past research topics does not match the priorities set by the SLV-PSP.